Pour des villes écoresponsables : contribution potentielle des élus municipaux et enjeux de formation associés. - Marc-André Guertin (VertigO)
The lack of political will is widely stated as a challenge for the socio-ecological transformation of cities. This article examines Quebec’s municipal elected officials as decision makers abled to transform cities into eco-responsible living environments and considers the knowledge and skill sets needed to induce such transformations. This article begins by identifying elected officials as actors within the Quebec political structures and draws attention to their ability to act on socio-ecological issues and highlights learning challenges they face as decision makers. The second part of this article presents the results of an analysis of the representations and practices of professionals involved in training of municipal elected officials to offer a critical appraisal of the socio-ecological issues and related skill sets they consider to be important. These results were drawn from a qualitative research approach based on non-participant observation and semi-structured interviews. Trainers of municipal officials interviewed present socio-ecological issues in a dualistic manner with a predominant focus on adaptation to climate change. They make little mention of the skills targeted by the training they offer. The training strategies mobilized can be associated to « knowledge transfer » and are influenced by a teaching paradigm. This critical exploration of the representations of trainers that work with local decision makers in Quebec shows the importance of pursuing research in environmental education with adults who are elected officials, as well as improving their professional training, particularly with respect to skills associated to eco-citizenship.